SOSOK KELUARGA PEJUANG DALAM NOVEL IBUK KARYA IWAN SETYAWAN: TINJAUAN PSIKOLOGI SASTRA - Indah Puspito Sari; Rusdian Noor Dermawan (CARAKA, 2016)
The purpose of this study was to describe (1) character and characterization, (2) setting, (3) planting values in the family, and (4) figures of family fighters in the novel Ibuk. Â The research was a qualitative research. The research data was qualitative data in the form of units of a paragraph or events in the novel Ibuk by Iwan Setiawan. The primary data source was the novel Ibuk by Iwan Setiawan published by PT. Gramedia Pustaka Utama Jakarta in 2012. The research instrument was a researcher herself that was equipped with a set of theories about the characters and characterizations, setting, cultivation of values, theory of literature and family psychology. Data collection methods were reading, recording, and literature. Data analysis methods were using qualitative descriptive. The results of the research are as follows. (1) The main character in the novel Ibuk is Ngatinah (Ibuk), while the subordinate figures are Mr, Bayek, Isa, Nani, and Rini. Ngatinah (Ibuk) is referred as the main character because she is the character most involved with the theme of the story, most interact with other characters and most take storytelling. Ngatinah character is depicted as a firm leader, responsible, humble, and patient. (2) In the novel Ibuk, setting the time, place, and the social culture is in it. Setting time shows a state that occurs by day, month, and year of occurrence. The setting of place occurs in the market, Batu Malang, Bogor, Surabaya, Karawang, and New York. The social setting takes place in the setting of social class or lower middle-level social class. (3) Investment value in the novel Ibuk family consists of (a) values are socialized parents in children include diligent worship, be honest, be respectful, harmonious with relatives and the community, and a way of learning achievement, and (b) how to disseminate the values in children, among others, to give advice and provide examples (exemplary). (4) The figure of a fighter in the novel Ibuk family is a family that struggles to improve the standard of living is better to work hard and cooperate with one another.